HCV genotypes distribution in patients from Botucatu, Bauru and Assis, São Paulo State, Brazil - Corvino, Sílvia M. (2006)
Hepatitis C is an infectious disease with variable clinical evolution, generally slow and progressive, caused by a RNA virus termed HCV (hepatitis C virus). This virus presents a structure composed by an external envelop, protein core, and a single strand RNA with approximately 9,5 Kb. RNA virus usually present a high mutation level resulting in diverse genomic sequences , and owing to these various genotypes and subtypes are evolved. HCV genotypes 1, 2 and 3 have been worldwide disseminated, being types 4 and 5 specially in Africa, and type 6 has been found in Asia. In Brazil the mostly frequent genotypes are 1, 2, and 3. The present study evaluated 1.018 plasma samples anti-HCV positive on ELISA assay, and HCV RNA positive by means of RT-PCR (Roche®). These plasma samples were sent from following cities of São Paulo state: Botucatu (N=508), Bauru (N= 415), and Assis (N= 95). Genotyping was performed by means of LiPA (Line probe assay - Bayer) which allows to analyze six HCV genotypes, and the most common subtypes. HCV genotypes regional distribution was 62.9% of genotype 1 ,and 34.5% of genotype 3 . Genotype 2 was found in Botucatu and Bauru regions only in a frequency of 2.1%, and genotype 5 was shown in Botucatu (0.2%) only . HCV subtypes distribution was as follow: in Botucatu region – subtype 1a (25%), 1b (29.3%), 1a/1b (3.5%), 2b (0.6%), 3a (35.0%), 5a (0.2%); in Bauru region – subtypes 1a (31.1%), 1b (27.2%), 1a /1b (2.4%), 2 b (1.9%), 2 a/2c (0.2%), 3a (32.3%); in Assis region – subtypes 1a (26.3%), 1b (26.3%), 1a /1b (2.1%), 3a (41.1%). The used genotyping technique did not allow to perform the subtypes characterization in 4.1% of samples. The HCV genotypes distribution in these São Paulo state regions was similar to those observed in other Brazilian and world sites, although some regional differences on HCV subtypes were observed , such as the occurrence of African genotypes (5 and 5a) in Botucatu region.